The Impact on Employee Productivity in the Indian IT Industry Sector Due to the COVID-19 Outbreak and Strategies for Recovery - Roy, Sugata (Digital Repository of Theses, 2025)
Background It is observed that employee productivity decreases with changes in working patterns and conditions. Similarly, employee productivity has reduced to a significant level in the Indian IT industry during the early days of remote work due to the rapid increase in Covid-19 cases in India in 2020. As stated by Sengupta and Jha, (2020, p. 1-3), due to the lack of suitable digital infrastructure and lack of remote-working experience, Indian IT employees performed below average. However, Indian IT companies have taken necessary steps to improve employee productivity during remote work. Methods A mixed data collection strategy has been used in this research where both qualitative and quantitative data have been collected through surveys and interviews. 200 general employees and 30 senior employees of the Indian IT sector have been surveyed while some managerial post holders have been interviewed to collect the responses of working-class people of the Indian IT sector. Results It is found that most respondents have cast their votes in favour of remote work, as they believe that they can perform well in this particular style. However, certain factors have been discovered that have distinct negative and positive effects on the productivity of an employee in the Indian IT sector. Discussion and conclusion It is observed from the data analysis that flexible work timing, suitable training programs, and technical assistance from the company are some positive inducers of employee productivity. On the other hand, failure to maintain the work-life cycle and strong cybersecurity system could be detrimental to the productivity of an employee. Moreover, it is noticed that there is a great opportunity to expand this research in the future by taking small and medium-sized enterprises into the count.